Efficacy of different light-emitting diodes (LEDs) attached to yellow sticky cards to capture the whitefly trialeurodes vaporariorum = Eficacia de diferentes diodos emisores de luz (LEDs) unidos a trampas adhesivas amarillas para la captura de la mosca blanca Trialeurodes vaporariorum - Castresana, Jorge Eduardo; Puhl, Laura Elena (Universidad de Nariño, Colombia, 2018)
Since adult insects respond to particular wavelengths, some investigations have proposed to use such behavior as potential target for novel monitoring and pest control tools.Yellow sticky cards have been commonly used for monitoring whiteflies population in open-fields as well as in greenhouses. However, the attractiveness depends on various factors such as the reflected intensity (brightness) and the hues of yellow color (wavelength) of the trap surface, which is often influenced by environmental conditions and may sometimes affect the capture of white flies.There fore, the use of light emitting diodes (LEDs) can be a significant complementary tool to strengthen attractiveness and the selectivity of these cards. This research was carried out to investigate the efficacy of the yellow sticky traps equipped with LEDs in the capturing mechanism of adult whiteflies Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae). This study has taken place in a glass little greenhouse at the Argentine Agricultural Experiment Station (EEA) of the National Institute for Agricultural Technology (INTA) of Concordia, Province of Entre Rios (Argentina), where rearing insect cages were placed together with tobacco plants, Solanum tabacum L. and beans Phaseolus vulgaris L. from June to July, 2013. The yellow sticky traps covered an area of 64cm2and were supplemented with LED sof different wavelengths, namely green LEDs (525 nm), UV (380 nm) and without LED sas control treatment. The trials showed that adults of T. vaporariorum on average preferred (α>0,05) traps equipped with green LEDs (525nm),which could have a promising use in greenhouses for the identification, monitoring and control of whiteflies